The Ideological Construction of Arab Mass Media on the Issue of Indonesia's Rejection of Israel - Khairunnisa, Annisa; Wahyudi, Jarot; Musthafa, Nurul Amin bin (Humanus, 2025)
The current study examines the ideology constructed by Al-Jazeera and CNN Arabic media on the issue of Indonesia's rejection of Israel at the U-20 World Cup 2023. The purpose of this research is to provide critical information and facts so that people can filter the news of Israel's rejection in Indonesia wisely. This research data is linguistic units in the Arabic mass media Al-Jazeera and CNN Arabic on March 30, 2023. Data was collected using the listening method, followed by tapping and recording techniques. The data were analyzed using the Padan method, which refers to Theo Van Leeuwen's critical discourse analysis (CDA). The results showed that Al-Jazeera media, through exclusion and inclusion, constructed public ideology not to justify Indonesia with negative representations. It was influenced by the ideology of Al-Jazeera's affiliate, Qatar, which has historically been religious and politically opposed to Israel. CNN Arabic strategizes language to construct public ideology through inclusion so that Indonesia is seen as a perpetrator of the rejection of Israel in a hostile, unprofessional, and anti-national manner. This was influenced because CNN Arabic is affiliated with America, which is a close friend of Israel in mutual economic and political relations.